Troubling Trends in Scientific Software Use - Joppa, Lucas; Harper, Richard; Takeda, Kenji; O'Hara, Kenton; Gavaghan, David; Emmott, Stephen (Science, 2013)
“Blind trust” is dangerous when choosing software to support research.